Forum junger Kunst 1981. - Schwarz, Martin; Kunstmuseum Düsseldorf; Kunsthalle Kiel (Wolfsburg : Städtische Galerie Wolfsburg, 1981)
Berent, Hella ; Bittermann, Caroline ; Bliese, Angelika ; Bohl, Peter ; Bonvie, Rudolf ; Bosslet, Eberhard ; Bradtke, Peter ; Bührenstedt-Metis, Catherine ; Bulla, Wolfgang ; Depenthal, Florian ; Dettmann, Udo ; Dudesek, Karel ; Engelhardt, KHY ; Enneper, Mic ; Neumann, Hartmut ; Pietryga, Stefan ; Rennertz, Karl Manfreid ; Zimmermann, Rolf ; etc.
Forum junger Kunst 1981, Städtische Galerie Wolfsburg, 10.5. - 7.6.1981 ; Kunstmuseum Düsseldorf, 11.7. - 16.8.1981 ; Kunsthalle zu Kiel, 6.9. - 18.10.1981
Duits
kunstcatalogus